Naphthalene Diimide-Ethylene Conjugated Copolymer as Cathode Material for Lithium Ion Batteries. Issue 2 (28th December 2016) - Zhang, Huicong; Xie, Yingpeng; Chen, Xiaoju; Jia, Tao; Huang, Wanrong; Luo, Suilian; Hou, Qiong; Zeng, Ronghua; Sun, Ziqi
Abstract : A large flat-conjugated copolymer poly[ethylene- N, N '-bis(2-ethylhexyl)-1, 4, 5, 8-naphthalene diimide] (PENDI), was synthesized through a simple synthetic method, which is preparation via 2, 6-dibromo- N, N '-bis(2-ethylhexyl)-1, 4, 5, 8-naphthalene diimide, and (E)-1, 2-bis(tributylstannyl) ethene via Stille coupling reaction for use as a cathode material for lithium ion batteries. The PENDI copolymer was characterized by IR, UV-vis spectra, 1 H NMR, and TGA. The electrochemical performance results demonstrated that the reversible capacity of PENDI can be retained at 85% of its initial theoretical capacity with a steady discharge voltage plateau of 2.0–2.5 V after 100 cycles at 0.1 C, and the coulomb efficiency remained above 98%. This can be attributed to the low solubility of the copolymer PENDI in electrolyte and the excellent structural stability of the copolymer PENDI during the charge–discharge tests. The synthesis of polymers with high conjugated systems and more stable structures will become a major breakthrough for the exploitation and optimization of cathode materials.